IMF Performance in the Run-Up to the Financial and Economic Crisis : IMF Surveillance in 2004-07. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2011)
The report assesses IMF surveillance in the period leading up to the global financial and economic crisis and offers recommendations on how to strengthen the IMF's ability to discern risks and vulnerabilities in the future. Chapters discuss the unfolding of the crisis and IMF messages prior to the crisis, and analyze the complex factors that influenced the IMF's performance in the run-up to the crisis. A companion CD provides background papers not included in this report.